Exploring the Synergy Between Microfinance and Poverty: A Bibliometric and Comprehensive Systematic Literature Review - Asmae Lahnech; Mustapha Chami (SAGE Open)
Microfinance has become an increasingly important instrument in the global battle against poverty. However, its long-term success and the hurdles it faces require further critical examination. The goal of this research is to critically evaluate the influence of microfinance on poverty reduction through a thorough analysis that combines bibliometric tools with a Systematic Literature Review (SLR) using the PRISMA framework. This dual-methodology approach seeks to offer a more comprehensive view of the present state of microfinance research and its implications for poverty alleviation. The bibliometric analysis identifies leading countries, academic institutions, journals, authors, and keywords in microfinance research, providing a global, multidisciplinary perspective on the field. The SLR focuses on 26 carefully selected scholarly articles, offering in-depth insights into key themes, current applications, challenges, and future directions of microfinance in poverty reduction. The findings show that, while microfinance has great promise for driving economic growth and promoting social inclusion, it also confronts significant challenges. Key findings include identification of high interest rates, repayment difficulties, and sustainability concerns among microfinance institutions as major obstacles. These findings highlight the need for focused interventions and innovative strategies for increasing microfinance’s efficacy in poverty alleviation. Finally, the study provides a strategic framework for stakeholders, including academics, policymakers, and practitioners, to effectively leverage microfinance as a sustainable tool for poverty reduction.